(untitled) (Journal of Psychiatrists’ Association of Nepal, 2021)
Hypothyroidism is associated with myriad of medical, neurological as well as psychiatric symptoms. There is classic association of depression with hypothyroidism and of mania occurring with hypothyroidism. Only few cases of mania associated with hypothyroidism are reported. This is the first case of mania associated with hypothyroidism in Nepalese patient. We report a case of 30-year-old female with symptoms of mania induced by primary hypothyroidism. She had no previous history of psychiatric disorder but her father was diagnosed depression. Psychosocial factors contributed to noncompliance of Tablet. Levo thyroxine. She was successfully managed with Tablet. Aripiprazole, thyroxine replacement, family therapy and psycho education sessions. Therefore, clinicians should be aware to assess thyroid function in patients presenting with mania, especially females with first episode. We should also evaluate for mania symptoms in cases of hypothyroidism. Psycho education of patient and family play vital role in the treatment process.